Birokrasi dan Peran Kaum Perempuan - Sedarmayanti Sedarmayanti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Man is the most essential factor in any organization. including the government bureaucracyÂ  embodied by the apparatus consisting of men and women. However, the concept of gender is still an issue in the term of apparatus.Â  This assumption is based on the fact showing the lack of sexual balance in the program design or development project and its implementation which results in the negligence of woman substance and aspiration that declines the woman. Thus, the bureaucracy reformation aimed at developing the government apparatus based on the gender balance should be continuously attempted. In addition, the competency development combined with the professionalism and corporate culture improvement should also be promoted, so the Indonesian apparatus will be characterized by the technical and managerial capability of international level. Â